Game E-Learning Code Master Dengan Konsep Mmorpg Menggunakan Adobe Flex 3 - Purnomo, Fredy; Leslivania, Monika; Daniel, Daniel; Cahya, Lisye Mareta (Bina Nusantara University, 2010)
The research objective is to design a web-based e-learning game that could be used to be a learning facility of C language programming and as an online game so it could be enjoyed by everybody easily in internet. Flex usage in this game online is to implement RIA (Rich Internet Application) concept in the game so e-learning process is hoped to be more interesting and interactive. E-learning game is also designed in MMORPG (Massively Multiplayer Online Role Playing Game) concept. The research method used is analysis and design method. Analysis method is done through literature study, user analysis, and similar game analysis. Meanwhile, design method is about monitor display, gameplay and system design. The conclution of this research is that this game provides an interesting learning media of C language program accordingly to subject material at class and also easier to use through website.